2007
DOI: 10.1007/s11596-007-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of multiple myeloma cell line treated by arsenic trioxide

Abstract: cDNA microarray was used to compare the gene expression profiles of multiple myeloma cell line RPMI8226 24 h before and after treatment with arsenic trioxide. Two cDNA probes were prepared by mRNA reverse transcription of both arsenic trioxide-treated and untreated RPMI8226 cells. The probes were labeled with Cy3 and Cy5 fluorescence dyes separately, hybridized with cDNA microarray representing 4096 different human genes, and scanned for fluorescence intensity. The differences in gene expression were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among TNFAIP8 variants. In order to determine the expression patterns of the variants in human tumors compared with normal tissue, we analyzed cataloged RNA-sequencing (RNA-seq) data from primary human tumor and normal tissue for 11 cancer types in The Cancer Genome Atlas (TCGA) (Figure 1a and Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among TNFAIP8 variants. In order to determine the expression patterns of the variants in human tumors compared with normal tissue, we analyzed cataloged RNA-sequencing (RNA-seq) data from primary human tumor and normal tissue for 11 cancer types in The Cancer Genome Atlas (TCGA) (Figure 1a and Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among Abbreviations: BrdU, 5-bromo-2'-deoxyuridine; ChIP-seq, chromatin immunoprecipitation sequencing; DOX, doxorubicin; Gadd45A, growth arrest and DNA damageinducible 45a; H3K4me1, histone H3 mono-methylation on lysine 4; H3K4me3, histone H3 tri-methylation on lysine 4; H3K27ac, histone H3 acetylation on lysine 27; p53RE, p53 response element; PCNA, proliferating cell nuclear antigen; Scri, cells expressing scrambled shRNA; shRNA, short hairpin RNA; TCGA, The Cancer Genome Atlas; TNFAIP8, tumor necrosis factor-α-induced protein 8; TP8i, cells expressing TNFAIP8 shRNA …”
mentioning
confidence: 99%
“…The effect of NREA on cell signalling pathways may differ, because it induces less oxidative DNA damage and is less genotoxic in comparison to ATO. REA treatment increases some genes, including CCL2 , CCL3 , BTG1 , TNFAIP3 , TNFAIP8 , SLC38A2 and IGFBP4 , associated with cell growth, cell‐cell signalling, regulation of apoptosis and cell homeostasis (Wang et al , ). Especially in MM, rearrangement or translocation of MYC is one of the most common events, resulting in activation of Myc pathway in patient MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 (Du and Ho 2001;Lu and Wang 2002;Luo et al, 2006;Wang et al, 2006, 2008b, Zhong et al, 2003 2. Monocytic Differentiation; 3.…”
Section: Appropriate Dosagementioning
confidence: 99%